Mengunyah Permen Karet Rasa Mint Karet Dapat Mengurangi Kecemasan Dalam Penyusunan Skripsi Mahasiswa Prodi Keperawatan Tingkat Akhir Program Ekstensi STIKIM 2021: Chewing Mint Can Reduce Anxiety in Writing Thesis of Nursing Study Program Students at the Final Level of the 2021 STIKIM Extension Program - Pratama, Gilang Patama; Lannasari; Solehudin (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: A way to reduce student anxiety in writing a thesis is chewing gum. Worry is reduced by reducing muscle tone and energy produced during chew.  This process is the first step based on digestion and raising genre saliva which resulting levels of cortisol. Objective: This study aims to examine the effect of chewing gum on anxiety levels in the preparation of the thesis of nursing study program students in the extension program conducted at the Advanced Indonesian Health Sciences College (STIKIM) in December 2021. Methods: The research design is a quasi (quasi-experiment) with Noneequivalent Control Group Design. This research was conducted by giving treatment to the experimental group and providing a control group as a comparison. The sampling technique is purposive sampling. The samples taken in this study were 42 respondents, the instrument used was mint-flavored chewing gum and the standard questionnaire was the ZSAS questionnaire. Results: From the results of univariate data testing, the age distribution of 47.4% is aged 24-34 years, with the gender with a percentage of 71.5% being female, then the percentage of religion, namely 88% is Islam, with a percentage of marital status 64.4 % are married and the last percentage of the length of thesis preparation 83.3% is less than six months. From the day of the bivariate test, it was found that there was an effect of chewing gum on decreasing anxiety levels with a p-value of 0.000. Discussion:  from the results of the research that has been carried out, it can be concluded that there is a decrease in anxiety levels in the preparation of a thesis in nursing study program students at the end of the extension program after chewing. chewing gum.